2012
DOI: 10.1038/ajg.2011.425
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation for Hepatocellular Carcinoma: 10-Year Outcome and Prognostic Factors

Abstract: OBJECTIVES:Radiofrequency ablation (RFA) is widely performed for hepatocellular carcinoma (HCC). However, there has been no report on 10-year outcome of RFA. The objective of this study was to report a 10-year consecutive case series at a tertiary referral center.METHODS:We performed 2,982 RFA treatments on 1,170 primary HCC patients and analyzed a collected database.RESULTS:Final computed tomography images showed complete tumor ablation in 2,964 (99.4%) of 2,982 treatments performed for the 1,170 primary HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
549
17
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(606 citation statements)
references
References 53 publications
32
549
17
8
Order By: Relevance
“…In the study by Nishikawa et al [26] , the reduction in OS observed in elderly patients compared with their younger counterpart was primarily due to the higher rate of early recurrence. Conversely, other studies have reported that old age was not a independent predictor of reduced survival after RFA [60][61][62] . Good safety profile of RFA is maintained in elderly and the rate of major complications was found to be similar in elderly and in younger cirrhotic patients [32] .…”
Section: Radiofrequency Ablationmentioning
confidence: 73%
See 1 more Smart Citation
“…In the study by Nishikawa et al [26] , the reduction in OS observed in elderly patients compared with their younger counterpart was primarily due to the higher rate of early recurrence. Conversely, other studies have reported that old age was not a independent predictor of reduced survival after RFA [60][61][62] . Good safety profile of RFA is maintained in elderly and the rate of major complications was found to be similar in elderly and in younger cirrhotic patients [32] .…”
Section: Radiofrequency Ablationmentioning
confidence: 73%
“…Studies on outcome after radiofrequency ablation (RFA) in elderly patients yielded conflicting results ( Table 2). In two retrospective studies performed on large series from Japan, old age emerged as an independent predictor of poor prognosis at multivariate analysis [61] . In the study by Nishikawa et al [26] , the reduction in OS observed in elderly patients compared with their younger counterpart was primarily due to the higher rate of early recurrence.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…This versatile use of platelet count and thrombocytopenia is supported by the multi-faceted etiology of decreased platelet count in chronic liver disease patients [1,5]. Indeed, the platelet count is incorporated into numerous diagnostic algorithms aimed at non-invasively assessing the severity of chronic liver diseases and features of portal hypertension, can be used to pinpoint patients at higher risk of developing hepatocellular carcinoma in population studies, and is a predictor of death in cirrhotic patients with and without hepatocellular carcinoma [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is currently recognized as an effective local treatment for HCC [5,6] and has been shown to be a relatively low risk procedure [7][8][9] . However, deterioration of liver function has been observed during the long-term follow-up of these patients [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%